Analysis of Factors Affecting The Success of Strategic Change Initiatives in The Management Consulting Sector - Salem AlNajem, Hosam (Research Parks Publishers, 2025)
Strategic change initiatives are essential tools that companies use to improve performance and achieve long-term goals. This study aims to analyze the factors influencing the strategic change initiative in a management consulting firm in Jeddah, Saudi Arabia. Quantitative analysis was used through a survey using a questionnaire distributed electronically to 100 employees, and the researcher received 81 response o. The research conducted a statistical analysis of the questionnaire to identify the success and failure factors affecting the initiative and evaluate the company’s performance. The results showed that effective communication with employees and developing a clear change message were critical factors that contributed to the success of the initiative. Clearly communicating the change vision to employees helped enhance their understanding of and commitment to the initiative’s goals, while the active participation of all members affected by the change was essential to achieving success. The commitment and support of senior management also played a vital role in directing and implementing the initiative. On the other hand, the results showed that resistance to change, the absence of standard principles, and adopting short-term initiatives without considering long-term goals were the main factors hindering the achievement of the initiative’s goals. Other obstacles included hiring non-specialized employees, lack of integration in project management, and effective monitoring of processes. The results showed that the initiative had a positive impact on the company’s performance, as employee satisfaction and the quality of services provided improved, customer satisfaction increased, and productivity and performance efficiency improved.